Optimization of Biodiesel Production from Candlenut Oil via Simultaneous Reaction Using a Bifunctional CeO2.CaO Catalyst - Widayat, Widayat (International Journal of Renewable Energy Development, 2025)
The biodiesel synthesis process with a high free fatty acid content can be accomplished in a single stage using solid catalysts that function simultaneously as both base and acid catalysts. In this study, CeO₂.CaO was used as a bifunctional catalyst for biodiesel synthesis from candlenut seed oil. Catalyst characterization includes FTIR, BET, SEM-EDX, and TPD analysis. Process optimization was carried out using the central composite design method on Design Expert software. To determine the effect of each process variable on the simultaneous reaction, the effect of methanol-to-oil molar ratio, catalyst loading, and reaction temperature on FAME yield was also analyzed. The optimum operating conditions to achieve high FAME yield were found at methanol-to-oil molar ratio of 10.3:1, 5.39% w/w catalyst loading, and a reaction temperature of 60°C.